Evolutionary Genetics of an S-Like Polymorphism in Papaveraceae with Putative Function in Self-Incompatibility - Paape, Timothy (Public Library of Science, 2011)
BACKGROUND: Papaver rhoeas possesses a gametophytic self-incompatibility (SI) system not homologous to any other SI mechanism characterized at the molecular level. Four previously published full length stigmatic S-alleles from the genus Papaver exhibited remarkable sequence divergence, but these studies failed to amplify additional S-alleles despite crossing evidence for more than 60 S-alleles in Papaver rhoeas alone. METHODOLOGY/PRINCIPAL FINDINGS: Using RT-PCR we identified 87 unique putative stigmatic S-allele sequences from the Papaveraceae Argemone munita, Papaver mcconnellii, P. nudicuale, Platystemon californicus and Romneya coulteri. Hand pollinations among two full-sib families of both A. munita and P. californicus indicate a strong correlation between the putative S-genotype and observed incompatibility phenotype. However, we also found more than two S-like sequences in some individuals of A. munita and P. californicus, with two products co-segregating in both full-sib families of P. californicus. Pairwise sequence divergence estimates within and among taxa show Papaver stigmatic S-alleles to be the most variable with lower divergence among putative S-alleles from other Papaveraceae. Genealogical analysis indicates little shared ancestral polymorphism among S-like sequences from different genera. Lack of shared ancestral polymorphism could be due to long divergence times among genera studied, reduced levels of balancing selection if some or all S-like sequences do not function in incompatibility, population bottlenecks, or different levels of recombination among taxa. Preliminary estimates of positive selection find many sites under selective constraint with a few undergoing positive selection, suggesting that self-recognition may depend on amino acid substitutions at only a few sites. CONCLUSIONS/SIGNIFICANCE: Because of the strong correlation between genotype and SI phenotype, sequences reported here represent either functional stylar S-alleles, tightly linked paralogs of the S-locus or a combination of both. The considerable complexity revealed in this study shows we have much to learn about the evolutionary dynamics of self-incompatibility systems.